The Assistance in Preparing Financial Statements for MSMEs Based on Financial Accounting Standards for MSMEs - Yulianti, Vista; Oktaviano, Benny; Wulandari, Dian Sulistyorini; Alfansyah, Putri Edelweis Aprilia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper discusses the implementation and outcomes of the Assistance in Preparing Financial Statements for MSMEs Based on Financial Accounting Standards for MSMEs in the Tambun Selatan program, which aims to address the financial management challenges faced by MSMEs in the region. The program followed a structured approach, starting with a preliminary needs assessment, followed by workshops, hands-on training, personalized mentoring, and feedback collection. The results indicate significant improvements in participants' knowledge of Financial Accounting Standards for MSMEs, their ability to prepare compliant financial statements, and their adoption of digital tools for financial reporting. Pre- and post-training evaluations revealed that 92% of participants demonstrated a strong understanding of Financial Accounting Standards for MSMEs, 76% were able to prepare accurate financial statements, and 68% began using accounting software.